Implikasi Penerapan Restorative Justice terhadap Putusan Pemidanaan di Pengadilan Negeri Kediri - Moch. Choirul Rizal (Universitas Muhammadiyah Yogyakarta, 2023)
The application of restorative justice can only be applied to certain criminal acts. However, this limitation was penetrated by the judge at the Pengadilan Negeri (PN) Kediri. This situation causes legal uncertainty. Therefore, this study focuses on the suitability of the application of restorative justice with the principles of restorative justice and its implications for sentencing decisions in the PN Kediri. This normative legal research uses a statute approach, case approach, and conceptual approach with research sources in the form of secondary data which includes primary, secondary, and non-legal legal materials. As a result, the application of restorative justice in sentencing decisions in the PN Kediri has not been intended to provide recovery to victims and there is no open space for participation for parties involved and affected by the criminal acts that occurred, except for the Decision of PN Kediri Number 204/Pid.B/ 2014/PN.Kdr, October 2, 2014; and Decision of PN Kediri Number 144/Pid.B/2016/PN.Kdr, dated August 15, 2016. Most of the restorative justice implementations are still at the “can be restorative” stage. The application of the concept of restorative justice in this case has implications for the number of prison sentences imposed by the judge at the PN Kediri.